RIWAYAT KEHAMILAN DAN PERSALINAN DENGAN KEJADIAN POSTPARTUM BLUES PADA IBU NIFAS DI KUDUS - Dwi Astuti; Yulisetyaningrum Yulisetyaningrum; Nasriyah Nasriyah; Atun Wigati (Jurnal Ilmu Keperawatan dan Kebidanan, 2023)
Giving birth is a woman's greatest gift and a very happy moment. Labor can also be a frightening state. Women who give birth often experience sadness and anxiety that affect their emotions. Postpartum blues is a mental disorder that occurs on day 1 after birth. Internal factors that influence postpartum blues are hormonal, psychological and personal fluctuations, previous depression, complications of pregnancy and childbirth. External factors are: caesarean section, unwanted pregnancies, low birth weight babies and mothers who have difficulty breastfeeding and caring for the baby. The prevalence of postpartum blues varies from 10 to 34 percent of all births in various countries. The incidence of postpartum blues in Japan ranges from 26 to 85%. About 20% of women who have recently given birth worldwide suffer from postpartum blues. Explanation of the relationship between pregnancy and childbirth with postpartum blues. Method: Correlation Analysis Study. using a cross-sectional approach. A sample of 64 postpartum mothers used a random sampling technique. Data were analyzed using the chi-square statistical test. Score: There is a relationship between previous pregnancies and postpartum blues with a P-value of 0.002 danlt; 0.05 and the probability is 5.682. There is a relationship between history of childbirth and postpartum blues, with a P-value of 0.023 danlt; 0.05 and the probability is 3,600. Diploma: There is a relationship between social support and the child's condition with the onset of postpartum blues.